การคัดเลือกสายต้นไผ่ซางหม่นที่มีศักยภาพในการผลิตชีวมวล - พวงจิก, ธัญพิสิษฐ์; หาระโคตร, พรชัย; บัวชุม, กุลรัตน์ (Thai Journal of Science and Technology, 2020)
The purpose of this study was to select bamboo (Dendrocalamus sericeus Munro) clones, which have a potential for biomass production. The top ten with three-year-old bamboo clones were selected from 211 clones, based on physical properties. The selected bamboo clones included the clones number 44, 53, 71, 83, 89, 101, 106, 120, 206 and 211.The selected bamboo clones were brought to the carbonization process (at a temperature of 500 °C with 1 hour holding time), then ground into charcoal powders, followed by analyses of chemical properties, heat value and ash content. Other parts of dried bamboo were measured for moisture content. The results indicated that various bamboo clones showed significant differences of heat values and ash contents. However, their moisture contents have no significant difference. The bamboo clone number 44 gave the highest heat value (6,963.7 cal/g), with no significance with that of the clone number 120 (6,957.6 cal/g). Moreover, the bamboo clone number 120 has the lowest ash content (2.04%). Therefore, the bamboo clone number 120 has a high potential as a material to produce biomass.